Healthy Active Successful Aging - Özdemirkan, Tuba; Şenlik, Zeynep Belma; Şimşek, A. Çiğdem (Turkey Health Literacy Journal, 2020)
People in Turkey are living longer and the rate of “NewBirth have fallen and are currently on the decline.We are becoming a population of “OLD PEOPLE”Both Globally and Nationally we are seeing that the ageingg population is on the INCREASE.It might sound “funny”but there will be more old people then young people in the world.According to recent studies on ‘Ageing and Population’,figures have shown that in the Year 2017 alone that in Turkey the Ageing population had risen by 8.5%. Pre Census population anticipate that current Ageing trends show a 10.2% increase for the year 2023 and a 27.7% for the year 2075 nationally.The data indicates that the ‘Ageing’population rates are further on the increase and for some years those figures will even increase very ‘sharply’.The evidence shows that whislt there was a 12.6% increase for the year 2017 alone,a 15.2% increase for the year 2023 and a ‘staggering’ 25.3% for the year 2040 in our Ageing Population is well estimated according to current ageing trends nationally.With the increase in our Ageing Population on the increase and well estimated for the years ahead,there poses many health challenges for our Health Care System both Nationally and Globally.Our rapid increasing Ageing population will bring with them many Chronic Health Issues and problems.At the National level we will see a large number of Serious Health Problems arise in the Age groups of people in the (65+)and over.We can see with the current Global picture that Medical Issues in the Ageing puts ‘strain’ on Health Systems and their ability to cope.At the National level, after analyzing all the figures it is well documented that we must have strategies in place in order to successfully provide and promote a stable and functional Health System for our Ageing Population.We at a National Level must strategically address those issues now in order to be better prepared for the years to come.With all the numbers and figures highlighting the increase in Chronic Health Problems “more the ones associated with the ageing process”then what can we do as ‘Health Care Givers,Health Managers and Health promoters do There are 5(Five) areas that we need to address for ‘Healthy Ageing’ and ‘Healthy Active Ageing’.The areas that need to be addressed for our “Ageing Population are their “PSYCHOLOGICAL,SOCIAL,PHYSICAL,RELIGOUS AND ECONOMIC” requirements.We then ‘procatively’ address the needs of our Ageing Population “HOLISTICALLY”.It is ‘fundamentally’ significant that these areas are acted upon.It is of vital importance that at the National Level we have ‘Strategic Plans,promotions and activities in place in order to better serv our Ageing Community and sustain a well adapted Health System for the coming years ahead.
Keywords: Healthy Living; Pro-Active Ageing; Health In The Elderly